Sensory Perception in Cetaceans: Part II—Promising Experimental Approaches to Study Chemoreception in Dolphins - Kremers, Dorothee; Célérier, Aurélie; Schaal, Benoist; Campagna, Sylvie; Trabalon, Marie; Böye, Martin; Hausberger, Martine; Lemasson, Alban (Frontiers in Ecology and Evolution, 2016)
Chemosensory perception in cetaceans remains an intriguing issue as morphological, neuroanatomical and genetic studies draw unclear conclusions, while behavioral data suggest that dolphins may use it for food selection or socio-sexual interactions. Experimental approaches have been scarce due to the practical difficulties of testing chemoreception in wild dolphins. Go/no-go tasks are one elegant way to investigate discrimination abilities; however, they require to train the animals, thus preventing spontaneous responses and hence the expression of preferences. Here, we aimed at testing potential spontaneous responses to chemical stimuli and developed novel procedures. First, we conducted a study to test whether captive dolphins respond to a biologically relevant smell. Therefore, we placed dead fish within an opaque barrel at the border of the pool and counted the number of respirations at proximity as an indicator of investigation. The same dead fishes were presented several times during experiments lasting three consecutive days. From the second day on (i.e. when the odor composition changed), dolphins breathed more often close to the fish-smelling barrel than close to the visually identical but empty control barrel. Second, we conducted a study to test whether dolphins are able to discriminate food flavors. Captive dolphins are commonly provided with ice cubes as a source of enrichment. We took this opportunity to provide ice cubes with different flavors and to compare the reaction to these different flavors as a measure of discrimination. Hence, we used the latency of return to the ice cube begging spot as a measure of discrimination from the previous ice cube flavor. Thus, our method used a non-invasive and easily replicable technique based on the spontaneous begging responses of dolphins toward more or less attractive items bearing biological relevance. The procedures used enabled us to show that dolphins may discriminate odors and flavors respectively.